Cooperação técnica brasileira em Moçambique: Discurso teórico de Cooperação Sul-Sul e o ProSAVANA - Lopes, Marcelo Rodrigues (2018)
Brazil has become a major player in South-South Cooperation (SSC). Especially since the Lula Government, the growth of Brazil's role as an international donor has gained significant strength.In this work, we will try to analyze the Brazilian performance in ProSAVANA as an international donor, in order to find out if Brazil follows the principles of South-South Cooperation in practice. In order to infer the behavior of Brazilian cooperation in the program, an investigation will be carried out on the concept of South-South Cooperation, pointing out its principles and objectives. In this process, the theme of International Technical Cooperation will be deepened, modality in which ProSAVANA finds itself. Finally, the observed results of ProSAVANA will be studied from different perspectives.